Fixed Point Theorem for Cyclic Weakly Generalized Contraction Mapping of Ciric Type - Goyal, S.; Garg, M. (Journal of Scientific Research, 2020)
In this article, the concept of cyclic weakly generalized contraction mapping of Ciric type has been introduced and the existence of a fixed point for such mappings in the setup of complete metric spaces has been established. Result obtained extends and improves some fixed point results in the literature. Example is also given to show that class of contraction mappings introduced in the paper is strictly larger class than the class of mappings used in the literature and thus ensures wider applicability of the result by producing the solutions to new problems.